382 Measuring Daytime Sleepiness in Insomnia Disorder. (3rd May 2021) - Manber, Rachel; Simpson, Norah; Dietch, Jessica; Tutek, Joshua; Tully, Isabelle
Abstract: Introduction: The EPWORTH Sleepiness Scale (ESS) is correlated with clinical parameters among patients with obstructive sleep apnea. However, its clinical relevance among patients with insomnia disorder is not clear. These patients often do not report daytime sleepiness nor have abnormal MSLT scores, but many do experience sleepiness in the evening. As a result, the ESS may not be the most appropriate measure for assessing daytime sleepiness among insomnia patients. This study aimed to evaluate clinical correlates of ESS among patients with insomnia. It also examined correlates of two items from the PROMIS item bank that specifically probe daytime sleepiness. Methods: We used baseline data from 141 participants with insomnia disorder (mean age = 63.1y [SD 8.2]; 72% female) in the RESTING study (RCT of the Effectiveness of Stepped-Care Sleep Therapy In General Practice). Clinical measures: the Insomnia Severity Index (ISI), the Geriatric Depression Scale (GDS), and the Morningness Eveningness Questionnaire (MEQ). ESS>10 defined excessive sleepiness. Two PROMIS items assessed frequency of being sleepy and of having trouble staying awake during the day, with ratings of 'quite a bit' and 'very much' classified as excessively sleepy. Results: The ESS did not correlate with any of the clinical variables (ISI, GDS, MEQ). Correlations with these three variables with the PROMIS Sleepiness were .36, .22, and -.24 and with the PROMIS Excessive Sleepiness .28, .31, and -.17. Of the 38 participants with ESS>10, 80% were not excessively sleepy per PROMIS. PROMIS Excessive Sleepiness classified only 9 participants as excessively sleepy, of which 7 (78%) were not classified by the ESS as excessively sleepy. Conclusion: These results suggest that the ESS might not be a clinically relevant measure among people with insomnia disorder and that the PROMIS items may better capture sleepiness and excessive sleepiness during the daytime in this patient group. The divergence of the two measures might relate to whether instructions specify daytime as the period assessed, since people with insomnia may be more likely to experience evening, rather than daytime, sleepiness. It might also relate to differences in item wording (i.e., struggling to stay awake [PROMIS] versus likelihood of falling asleep [ESS]). Support (if any): 1R01AG057500